2016
DOI: 10.1021/acs.cgd.6b00639
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Drug Multicomponent Crystals as an Effective Technique to Overcome Weaknesses in Parent Drugs

Abstract: An interesting multicomponent crystal consisting of drug–drug combination was synthesized. The multidrug crystals consisted of antidiabetic drugs glicalzide and metformin. Single crystal X-ray structure analysis revealed that this multicomponent crystal is salt-type multicomponent crystal. The physicochemical properties of this crystal were significantly different from those of the parent drugs. The multicomponent crystal showed impressive solubility and dissolution rate compared to that of the raw material of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 45 publications
1
46
0
1
Order By: Relevance
“…As described earlier, in the piperine-succinic acid cocrystal, succinic acid molecules formed a channel structure. Solubility enhancements arising from a channel structure have been reported previously, and this piperine-succinic acid cocrystal structure strongly indicated the occurrence of this improvement mechanism [56,57]. Putra et al explained the mechanism as follows [58]: First, the more highly soluble coformer molecules dissolve from a cocrystal, leaving void channel structure in the crystal.…”
Section: Resultssupporting
confidence: 51%
“…As described earlier, in the piperine-succinic acid cocrystal, succinic acid molecules formed a channel structure. Solubility enhancements arising from a channel structure have been reported previously, and this piperine-succinic acid cocrystal structure strongly indicated the occurrence of this improvement mechanism [56,57]. Putra et al explained the mechanism as follows [58]: First, the more highly soluble coformer molecules dissolve from a cocrystal, leaving void channel structure in the crystal.…”
Section: Resultssupporting
confidence: 51%
“…Putra et al reported [92] a multidrug crystal of antidiabetic drug gliclazide (GLI) and metformin (MET). Combining these two non-insulin-dependent diabetes mellitus (NIDDM) drug, they have prepared a salt that is more soluble and have higher dissolution rate compared to GLI; and less hygroscopic compared to MET.…”
Section: Gliclazide-metformin Saltmentioning
confidence: 99%
“…200 Formation of drug-drug pharmaceutical co-crystals results to overcome the problems related with a traditional combination of drugs by modifying the properties of both drugs. 59,198,203 Telmisartan: Atenolol co-crystals 204 proved that multidrug co-crystals could be a great replacement for standard therapy with more than one API. Almansa prepared tramadol hydrochloride: celecoxib co-crystals which showed favourable physicochemical and dissolution profiles.…”
Section: Applicationsmentioning
confidence: 99%